Experimental study on shallow and deep dopant properties at the interface of PtOx/ZnO Schottky diodes. (1st June 2022) - Matsumura, Mikiya; Tanaka, Takahisa; Uchida, Ken
Abstract: The donor properties at the interface of the PtO x /ZnO Schottky diodes on hydrothermally grown ZnO were investigated. From the capacitance–voltage ( C–V ) characteristics of the diode and Hall effect measurements of the bulk substrate, we revealed that the carrier concentration at the ZnO Schottky diodes interface is much higher than that in the bulk. By utilizing the C–V characteristics and the deep level transient spectroscopy, we demonstrated that the interfaces have two kinds of ionized donors; the shallow and deep donors, whose activation energies were 4 meV and 0.33 eV, respectively. Both of the two types of donors were ionized near the interface, whereas only the low-concentration shallow donors were ionized in the bulk. The shallow and deep donors were assigned to hydrogen interstadials and E3 defects, respectively. Since both the donor types are related to hydrogens, annealing in the oxygen atmosphere was effective to greatly suppress the donor concentration at the diode interface.